Carbonate-doped high-activity fully-decomposed seawater electro-catalytic material as well as preparation method and application thereof

The carbonate-doped CO32--CoMoO4/Co3O4/NF composite prepared through two-step hydrothermal reaction solves the problem of insufficient chlorine corrosion resistance of sea hydroelectric catalysts in the prior art, and achieves efficient and stable seawater electrolysis, meeting the needs of industrial applications.

CN119685874AActive Publication Date: 2025-03-25SHANDONG UNIV

Patent Information

Application Number
CN202510085889.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-03-25
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The prior art is difficult to prepare highly active seawater electrocatalysts that are efficient and resistant to chlorine corrosion, limiting the efficiency and life of electrolyzing seawater to produce hydrogen.

Method used

Through two-step mild hydrothermal reaction, using three-dimensional metal foam nickel as the current collector, carbonate-doped CO32--CoMoO4/Co3O4/NF heterogeneous composite material has high activity and chlorine corrosion resistance.

Benefits of technology

The material can stably drive full-resolved seawater electrolysis at a lower potential, maintain catalytic performance for a long time, achieve the current density required by the industry, and significantly extend the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005250132200000011
    Figure HDA0005250132200000011
  • Figure HDA0005250132200000012
    Figure HDA0005250132200000012
  • Figure HDA0005250132200000021
    Figure HDA0005250132200000021
Patent Text Reader

Abstract

The invention provides a carbonate-doped high-activity full-decomposition seawater electro-catalytic material as well as a preparation method and application thereof. The preparation method of the material comprises the following steps: placing a pretreated foamed nickel (NF) current collector in a cobalt source aqueous solution, and carrying out a hydrothermal reaction; after the reaction is finished, cooling, washing and drying to obtain a Co3O4 / NF precursor composite material; placing the obtained Co3O4 / NF precursor composite material in a mixed solution containing a cobalt source, a molybdenum source, urea and sodium citrate, and carrying out a hydrothermal reaction; and after the reaction is finished, cooling, washing and drying to obtain the product. According to the preparation method, the three-dimensional metal foam nickel is taken as a current collector, the stable full-decomposition seawater electrocatalyst with high activity and chlorine corrosion resistance is prepared through two-step mild hydrothermal reaction, and the prepared composite catalyst can drive full-decomposition seawater to stably operate for a long time under a relatively low potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a carbonate-doped high-activity fully-lyzed seawater electrocatalytic material and a preparation method and application thereof, belonging to the field of electrocatalytic materials. Background Art

[0002] The over-exploitation and use of fossil fuels has led to a serious energy crisis. While these non-renewable energy sources provide energy for humans, they also inevitably emit a large amount of carbon dioxide, sulfur dioxide and other gases, causing greenhouse effects and environmental pollution, which is not in line with the goal of sustainable development for mankind. Hydrogen energy, as a clean, green, high-energy-density renewable clean energy, has no carbon emissions during the combustion process, and the product is only water. It is considered to be an ideal substitute for fossil fuels. Using electricity generated by abundant renewable energy (solar energy, wind energy, tidal energy, etc.) to drive water cracking has become a very promising hydrogen production technology, meeting the many requirements of mankind for emerging renewable energy sources that are efficient, low-carbon, economical, and environmentally friendly.

[0003] In recent decades, the technology of hydrogen production by electrolysis of water has developed rapidly. The electrolyte used in the electrolysis process mainly comes from fresh water (high-quality pure water or purified deionized water). Since fresh water accounts for less than 3% of the total global water resources and is mostly covered by glaciers and snow-capped mountains, its large-scale electrolysis of water is limited. In addition, in the process of preparing pure water / deionized water, complex purification processes and additional cost investment are often required, and a large amount of wastewater will be generated during the purification process, which does not meet the development requirements of economy and environmental protection. In contrast, seawater resources are very abundant, accounting for about 96.5% of the total global water resources, which can be said to be inexhaustible. Therefore, direct electrocatalytic decomposition of seawater to produce hydrogen is more economical and feasible, especially for coastal areas rich in renewable resources. Making full use of abundant renewable energy to efficiently and stably electrolyze seawater to produce hydrogen is of great significance for reducing environmental pollution, optimizing energy structure, alleviating freshwater shortage, and preparing high value-added products.

[0004] However, due to the complex composition of seawater, seawater contains a variety of ions (mainly Na + and Cl - In addition to the oxygen evolution reaction (OER) at the anode and the hydrogen evolution reaction (HER) at the cathode, the oxidation reaction of chloride ions (ClOR) will also occur during the electrolysis process. Among them, the ClOR side reaction will generate a variety of chlorine-containing byproducts that are toxic, polluting and corrosive to the environment, leading to damage to components such as catalysts, electrodes and electrolyzers, affecting the service life of electrocatalysts, and becoming the key to restricting hydrogen production by electrolysis of seawater. Therefore, the preparation of a highly active seawater electrocatalyst with high resistance to chlorine corrosion is crucial to improving the efficiency and life of seawater electrolysis.

[0005] Although researchers have tried to prepare a variety of seawater electrocatalysts and have made great improvements in improving chlorine resistance, it is still difficult to meet industrial standards. In addition, research often focuses on a single half-reaction (OER or HER), which makes it difficult to directly use it as a dual electrode for complete seawater splitting, further limiting the practical application of catalysts in complete seawater splitting. Therefore, the use of simple and economical methods to prepare highly active electrocatalysts for complete seawater splitting still needs further exploration. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a carbonate-doped high-activity electrocatalytic material for complete seawater decomposition, and a preparation method and application thereof. The present invention uses three-dimensional metal foam nickel as a current collector, and prepares a stable electrocatalyst for complete seawater decomposition with high activity and resistance to chlorine corrosion through two-step mild hydrothermal reaction. The prepared composite catalyst can drive the complete seawater decomposition to operate stably for a long time at a relatively low potential.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a carbonate-doped high-activity seawater electrocatalytic material comprises the following steps:

[0009] (1) placing the pretreated nickel foam (NF) current collector in a cobalt source aqueous solution for hydrothermal reaction; after the reaction is completed, cooling, washing, and drying to obtain a Co3O4 / NF precursor composite material;

[0010] (2) placing the Co3O4 / NF precursor composite material obtained in step (1) in a mixed solution containing a cobalt source, a molybdenum source, urea and sodium citrate to carry out a hydrothermal reaction; after the reaction is completed, cooling, washing and drying are performed to obtain CO3 2- -CoMoO4 / Co3O4 / NF heterogeneous composite material, that is, a carbonate-doped high-activity electrocatalytic material for the complete decomposition of seawater.

[0011] Preferably, according to the present invention, the pretreatment step in step (1) is: ultrasonically treating the nickel foam current collector in 1 mol / L HCl solution, deionized water, and anhydrous ethanol for 30 minutes respectively, and then vacuum drying at 60°C for standby use; the purpose of the pretreatment is to remove impurities such as oxides on the surface of the nickel foam.

[0012] Preferably according to the present invention, the thickness of the nickel foam in step (1) is 1.5-2.0 mm.

[0013] Preferably according to the present invention, the cobalt source in step (1) is Co(NO3)3·6H2O, and the concentration of the cobalt source aqueous solution is 0.02-0.03 mol / L.

[0014] According to the present invention, the volume of the cobalt source aqueous solution in step (1) is sufficient to completely cover the foamed nickel current collector.

[0015] Preferably, according to the present invention, the temperature of the hydrothermal reaction in step (1) is 150-180° C., and the hydrothermal reaction time is 10-12 h.

[0016] Preferably, according to the present invention, the washing in step (1) is performed by rinsing with deionized water for 3-5 times, and the drying is performed at 60-70° C. for 6-8 hours.

[0017] Preferably according to the present invention, the cobalt source in step (2) is Co(NO3)3·6H2O, and the molybdenum source is Na2MoO4·2H2O.

[0018] Preferably according to the present invention, the concentration of the cobalt source in the mixed solution in step (2) is 0.04-0.06 mol / L.

[0019] Preferably according to the present invention, the molar ratio of the molybdenum source to the cobalt source in the mixed solution in step (2) is 1:1, the molar ratio of urea to the cobalt source is 0.75-1.25:1, and the molar ratio of sodium citrate to the cobalt source is 0.2-0.3:1.

[0020] According to the present invention, the volume of the mixed solution in step (2) is sufficient to ensure that the Co3O4 / NF precursor composite material is completely submerged.

[0021] Preferably, according to the present invention, the temperature of the hydrothermal reaction in step (2) is 120-140° C., and the time of the hydrothermal reaction is 8-10 h.

[0022] Preferably, according to the present invention, the washing in step (2) is performed by rinsing with deionized water for 3-5 times, and the drying is performed at 60-70° C. for 6-8 hours.

[0023] The present invention also provides a carbonate-doped high-activity seawater electrocatalytic material prepared by the above-mentioned preparation method, wherein the electrocatalytic material comprises a nickel foam (NF) current collector and a heterogeneous composite material CO3 grown in situ on the nickel foam (NF) current collector. 2- -CoMoO4 / Co3O4; the heterogeneous composite material CO3 2- -The microstructure of CoMoO4 / Co3O4 is a combination of carbonate-doped hydrangea-shaped CoMoO4 nanoflowers and Co3O4 nanoparticles.

[0024] According to the present invention, the above carbonate-doped high-activity seawater electrocatalytic material is used as a seawater electrocatalyst for electrocatalytic seawater electrolysis.

[0025] The technical features and beneficial effects of the present invention are as follows:

[0026] 1. The raw materials of the carbonate-doped high-activity seawater electrocatalyst material of the present invention are cheap and easy to obtain, and the synthesis route is simple. Only two steps of mild hydrothermal reaction are required to prepare a high-activity seawater electrocatalyst with a heterogeneous structure. In the preparation method of the present invention, the concentration of urea added must be controlled. If the concentration of urea added is too low, the carbonate doping amount will be too low, affecting the activity of the catalyst and the full expression of the chlorine resistance. If the concentration of urea added is too high, excessive carbonate will be introduced to form partial carbonates, which will hinder the full expression of the active sites and reduce the catalytic performance of the electrolysis of seawater. At the same time, the preparation process of the present invention is simple, with low energy consumption and low equipment requirements. The prepared CO3 2- -CoMoO4 / Co3O4 / NF heterogeneous composite material has excellent performance in fully decomposing seawater, providing a feasible solution for the actual industrial application of fully decomposing seawater.

[0027] 2. The carbonate-doped high-activity electrocatalytic material for the complete decomposition of seawater CO3 obtained by the present invention 2- -CoMoO4 / Co3O4 / NF has a unique hydrangea-like structure, which can effectively increase the specific surface area of ​​the catalyst and expose more active sites. At the same time, the hydrangea-like nanoflower structure is an open structure, which is conducive to mass transfer and migration of gas products. In addition, carbonate, as an anionic group with a high charge load, can effectively regulate the charge distribution of the catalytic active center, and at the same time, through the strong electrostatic repulsion between it and the chloride ion, it effectively resists the contact and damage of the chloride ion to the catalyst material. In addition, the formation of a heterojunction between CoMoO4 and Co3O4 can improve the close contact between the catalyst interface, improve the charge transfer efficiency of the catalyst and the stability of the structure. Through the synergistic effect of carbonate doping and heterogeneous structure, the electrocatalytic material can effectively improve the activity and stability of the catalyst during the electrolysis of seawater. When dehydrogenating real seawater, only an overpotential of 101mV is required to reach 10mA / cm 2 When fully dissolving real seawater, only 1.86V is required to reach 100mA / cm 2 The current density can be kept stable for more than 30 hours with almost no performance degradation, and even only 2.18V is needed to reach the industrial requirement of 0.5A / cm 2 of current density.

[0028] 3. The carbonate-doped high-activity seawater electrocatalytic material prepared by the present invention is an in-situ grown self-supporting heterostructure composite material. In the process of electrocatalytic cracking of seawater, it can be directly used as a dual-electrode driven reaction, and there is no need to stick the catalyst on an additional conductive current collector, which simplifies the preparation process. At the same time, it avoids the problems of decreased conductivity caused by the introduction of binders such as Nafion and easy detachment of the catalyst under high current working conditions, thereby ensuring the high conductivity and high durability of the catalyst. The present invention provides a new synthesis idea and direction for the rational use of mild hydrothermal synthesis technology to prepare in-situ grown anionic group-doped high-activity seawater electrocatalysts through a simple and easy preparation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 CO3 prepared in Example 1 2- -X-ray diffraction (XRD) pattern of CoMoO4 / Co3O4 / NF electrocatalytic material.

[0030] Figure 2 CO3 prepared in Example 1 2- -Raman spectrum of CoMoO4 / Co3O4 / NF electrocatalytic material.

[0031] Figure 3 CO3 prepared in Example 1 2- -Scanning electron microscopy (SEM) image of CoMoO4 / Co3O4 / NF electrocatalytic material.

[0032] Figure 4 CO3 prepared in Example 1 2- -Element mapping of CoMoO4 / Co3O4 / NF electrocatalytic materials.

[0033] Figure 5 CO3 prepared in Example 1 2- -Polarization curves (LSV) of the CoMoO4 / Co3O4 / NF electrocatalytic material and the electrocatalytic materials prepared in Comparative Examples 1-6 in the hydrogen evolution performance test in simulated seawater.

[0034] Figure 6 CO3 prepared in Example 1 2- -Polarization curves (LSV) of the oxygen evolution performance test of the CoMoO4 / Co3O4 / NF electrocatalytic material and the electrocatalytic materials prepared in comparative examples 1-6 in simulated seawater.

[0035] Figure 7 CO3 prepared in Examples 1-5 2--Polarization curve (LSV) of the CoMoO4 / Co3O4 / NF electrocatalytic material in the hydrogen evolution performance test in simulated seawater.

[0036] Figure 8 CO3 prepared in Examples 1-5 2- -Polarization curve (LSV) of the oxygen evolution performance test of CoMoO4 / Co3O4 / NF electrocatalytic material in simulated seawater.

[0037] Fig. 9 CO3 prepared in Example 1 2- -Polarization curve (LSV) of the hydrogen evolution performance test of CoMoO4 / Co3O4 / NF electrocatalytic material in real seawater.

[0038] Fig.10 CO3 prepared in Example 1 2- -Polarization curve diagram (LSV) of the CoMoO4 / Co3O4 / NF electrocatalytic material in the electrocatalytic full decomposition of real seawater performance test.

[0039] Fig.11 CO3 prepared in Example 1 2- - Long-term stability test diagram of CoMoO4 / Co3O4 / NF electrocatalytic material under constant potential in electrolysis of real seawater.

[0040] Fig.12 This is a scanning electron microscope (SEM) image of the electrocatalytic material prepared in Comparative Example 4.

[0041] Fig.13 This is a scanning electron microscope (SEM) image of the electrocatalytic material prepared in Comparative Example 5.

[0042] Fig.14 This is a scanning electron microscope (SEM) image of the electrocatalytic material prepared in Comparative Example 6. DETAILED DESCRIPTION

[0043] The present invention is further described in detail below in conjunction with specific examples, but the protection scope of the present invention is not limited thereto.

[0044] Reagents and instruments: All reagents used in the present invention were of analytical grade and were used directly after purchase without further purification.

[0045] Cobalt nitrate hexahydrate (Co(NO3)3·6H2O), sodium molybdate dihydrate (Na2MoO4·2H2O), sodium citrate (C6H5Na3O7), urea (CH4N2O), sodium chloride (NaCl), potassium hydroxide (KOH), hydrochloric acid (HCl 36.0-38.0%), anhydrous ethanol (C2H6O) are available in Chinese medicine;

[0046] Nickel foam (NF) was purchased from Lizhiyuan Battery Sales Department in Yingze District, Taiyuan City, with a thickness of 1.5 mm.

[0047] Electronic balance (LA203E / A), electric constant temperature blast oven (Jinghong), magnetic stirrer (85-1 model), electrochemical workstation (Jiangsu Donghua, DH7001B).

[0048] Electrochemical test: The electrochemical test was conducted using a Jiangsu Donghua DH7001B electrochemical workstation. A three-electrode test system was used, in which the cut electrode material was directly used as the working electrode, the Ag / AgCl electrode was used as the reference electrode, the platinum sheet (1cm×1cm) electrode was used as the counter electrode, the simulated seawater electrolyte was a newly prepared 1mol / LKOH+0.5mol / LNaCl mixed solution, and the real seawater electrolyte was seawater from Qingdao waters. Unless otherwise specified, the test data were all 90% IR compensated.

[0049] Example 1

[0050] A method for preparing a carbonate-doped high-activity seawater electrocatalytic material comprises the following steps:

[0051] (1) The nickel foam was cut into 2 cm × 3 cm sizes, and the cut nickel foam was ultrasonically cleaned in 1 mol / L HCl solution, deionized water, and anhydrous ethanol for 30 min respectively, pretreated to remove oxides and other impurities on the surface of the nickel foam, and vacuum dried at 60 ° C for subsequent use; 1.0 mmol Co(NO3)3·6H2O was dissolved in 40 mL deionized water under stirring, and the obtained Co(NO3)3 solution was transferred to a 50 mL polytetrafluoroethylene liner, and then the pretreated nickel foam was inserted into the Co(NO3)3 solution, and the liner was sealed and transferred to a stainless steel reactor, which was sealed; the reaction was carried out at 160 ° C in an electric constant temperature forced air oven for 10 h, and then naturally cooled to room temperature; the reactor was taken out, the obtained product was rinsed with deionized water 3 times, and dried at 60 ° C for 8 h to obtain a Co3O4 / NF precursor composite material.

[0052] (2) Dissolve 2.0mmol of Co(NO3)3·6H2O, 2.0mmol of Na2MoO4·2H2O, 2.0mmol of urea and 0.5mmol of sodium citrate in 40mL of deionized water under stirring, transfer the obtained uniform mixed solution to a 50mL polytetrafluoroethylene liner, insert the Co3O4 / NF precursor composite material obtained in step (1) into the above mixed solution, seal the liner and transfer it to a stainless steel reactor, seal it. React in an electric constant temperature blast oven at 120℃ for 8h, then cool naturally to room temperature, finally take out the reactor, rinse the obtained product with deionized water 3 times, and dry it at 60℃ for 8h to obtain CO3 2- -CoMoO4 / Co3O4 / NF heterogeneous composite material, that is, a carbonate-doped high-activity electrocatalytic material for the complete decomposition of seawater.

[0053] The CO3 prepared in this example 2- -XRD patterns of CoMoO4 / Co3O4 / NF composites Figure 1 As shown, from Figure 1 It can be seen that the composite material is mainly composed of three phases: NF, Co3O4 and CoMoO4. No carbonate was found, indicating that carbonate is uniformly doped into the entire catalyst. Optical characterization of carbonate gives CO3 2- -Raman spectrum of CoMoO4 / Co3O4 / NF composite material Figure 2 As shown, at 600-800cm -1 There is obvious CO3 2- The characteristic peaks of CO3 2- -The successful construction of CoMoO4 / Co3O4 / NF composite material. The SEM image of the material in Example 1 is as follows Figure 3 As shown, it can be seen that the morphology of the sample is a combination of hydrangea-shaped nanoflowers and nanoparticles (circled parts), indicating the successful construction of heterogeneous structures. Among them, the nanoparticles are relatively small, with a size of 60-100nm, and the hydrangea-shaped CoMoO4 nanoflowers are composed of interlaced nanosheets. The diameter of the nanoflowers is 3±0.5μm, and the thickness of the nanosheets is 10-15nm. The unique hydrangea-shaped structure can increase the specific surface area of ​​the catalyst, which is conducive to the exposure of more active sites. At the same time, the open structure is conducive to promoting mass transfer and gas transport, and accelerating the process of the reaction. The resulting CO3 2- -Mapping spectrum of each element of CoMoO4 / Co3O4 / NF composite material Figure 4 As shown in the figure, it can be clearly seen that the four elements are evenly distributed throughout the hydrangea-like structure, further indicating that carbonate is evenly doped into the entire material.

[0054] The CO3 prepared in this example 2- -CoMoO4 / Co3O4 / NF composite materials were directly used as electrodes to test the electrolysis performance of seawater in simulated seawater and real seawater. The specific steps are as follows:

[0055] The electrochemical performance test was conducted using a Jiangsu Donghua DH7001B electrochemical workstation. A three-electrode test system was used, in which the prepared electrocatalyst was directly used as the working electrode, Ag / AgCl was used as the reference electrode, a platinum sheet (1 cm × 1 cm) electrode was used as the counter electrode, and the simulated seawater electrolyte was a newly prepared 1 mol / L KOH+0.5 mol / LNaCl mixed solution. The real seawater electrolyte was seawater from Qingdao. The test data were all subjected to 90% IR compensation, and all potentials were converted to reversible hydrogen potentials.

[0056] CO3 prepared in this example 2- -The hydrogen evolution performance of the CoMoO4 / Co3O4 / NF composite material was tested in a simulated seawater solution (1 mol / L KOH + 0.5 mol / L NaCl) at a linear scan rate of 5 mV / s. Figure 5 ) and oxygen evolution performance test ( Figure 6 ). As can be seen from the figure, the electrocatalytic material prepared in this embodiment reaches 100mA / cm 2 The current density only requires 219mV overpotential; when conducting electrocatalytic oxygen evolution reaction tests, it reaches 100mA / cm 2 The current density only requires an overpotential of 310 mV, which is significantly better than that of Comparative Examples 1-6 and Examples 2-5 and most of the reported oxide electrocatalysts, indicating that the material has excellent seawater electrolysis performance. Based on this, it was further used for direct electrolysis of real seawater tests, and it was found that when the material was tested for hydrogen production performance by electrolysis of real seawater, an overpotential of only 101 mV was required to reach 10 mA / cm 2 The current density ( Fig. 9 ), when fully dissolving real seawater, only 1.86V of potential is required to reach 100mA / cm 2 The current density ( Fig.10 ) and can maintain a stable reaction for more than 30 hours with almost no performance degradation ( Fig.11 ), even only 2.18V is needed to reach the 0.5A / cm required by industry. 2 The current density ( Fig.10 ), the above results prove that the material of Example 1 has excellent full solution of seawater performance.

[0057] Example 2

[0058] A method for preparing a carbonate-doped high-activity seawater electrocatalytic material is as described in Example 1, except that the amount of urea added in step (2) is 1.5 mmol.

[0059] The electrocatalytic material prepared in this example was applied to electrocatalytic cracking of seawater in a simulated seawater solution, and the hydrogen evolution performance and oxygen evolution performance were tested as described in Example 1.

[0060] The electrocatalytic material prepared in this example reached 100 mA / cm 2 The current density required an overpotential of 264 mV; when conducting the electrocatalytic oxygen evolution reaction test, it reached 100 mA / cm 2 The current density requires an overpotential of 363 mV. The overpotential values ​​of hydrogen evolution and oxygen evolution reactions of the catalyst in this embodiment for electrolysis of seawater are higher than those in Example 1, indicating that the catalytic performance of this embodiment is slightly lower than that of Example 1.

[0061] Example 3

[0062] A method for preparing a carbonate-doped high-activity seawater electrocatalytic material is as described in Example 1, except that the amount of urea added in step (2) is 1.75 mmol.

[0063] The electrocatalytic material prepared in this example was applied to electrocatalytic cracking of seawater in a simulated seawater solution, and the hydrogen evolution performance and oxygen evolution performance were tested as described in Example 1.

[0064] The electrocatalytic material prepared in this example reached 100 mA / cm 2 The current density required an overpotential of 239 mV; when conducting the electrocatalytic oxygen evolution reaction test, it reached 100 mA / cm 2 The current density requires an overpotential of 360 mV. The overpotential values ​​of the hydrogen evolution and oxygen evolution reactions in this embodiment are higher than those in Example 1, indicating that the catalytic performance of this embodiment is slightly lower than that in Example 1.

[0065] Example 4

[0066] A method for preparing a carbonate-doped high-activity seawater electrocatalytic material is as described in Example 1, except that the amount of urea added in step (2) is 2.25 mmol.

[0067] The electrocatalytic material prepared in this example was applied to electrocatalytic cracking of seawater in a simulated seawater solution, and the hydrogen evolution performance and oxygen evolution performance were tested as described in Example 1.

[0068] The electrocatalytic material prepared in this example reached 100 mA / cm 2The current density required an overpotential of 227mV; when conducting the electrocatalytic oxygen evolution reaction test, it reached 100mA / cm 2 The current density requires an overpotential of 347 mV. The overpotential values ​​of the hydrogen evolution and oxygen evolution reactions in this embodiment are slightly higher than those in Example 1, indicating that the introduction of too much carbonate ions will hinder the full expression of the catalytic activity and reduce the catalytic performance, making the catalytic performance of this embodiment slightly lower than that of Example 1.

[0069] Example 5

[0070] A method for preparing a carbonate-doped high-activity seawater electrocatalytic material is as described in Example 1, except that the amount of urea added in step (2) is 2.5 mmol.

[0071] The electrocatalytic material prepared in this example was applied to simulated seawater solution for electrocatalytic cracking of seawater, and the hydrogen evolution performance and oxygen evolution performance were tested as described in Example 1.

[0072] The electrocatalytic material prepared in this example reached 100 mA / cm 2 The current density required an overpotential of 248 mV; when conducting the electrocatalytic oxygen evolution reaction test, it reached 100 mA / cm 2 The current density requires an overpotential of 358 mV, and the overpotential values ​​are all higher than those in Example 1. This may be due to the introduction of too many carbonate ions, which further hinders the expression of catalytic activity, resulting in the catalytic performance of this example being lower than that of Example 1.

[0073] Comparative Example 1

[0074] The pretreated nickel foam is directly used as the seawater electrocatalytic material, and the pretreatment process is as described in Example 1.

[0075] The electrocatalytic material obtained in this comparative example was applied to electrocatalytic cracking of seawater in a simulated seawater solution, and the hydrogen evolution performance and oxygen evolution performance were tested as described in Example 1.

[0076] When the electrocatalytic material prepared in this comparative example is tested for electrocatalytic decomposition of simulated seawater, within the selected test voltage range, the electrocatalyst material cannot reach 100 mA / cm2 in either the electrocatalytic hydrogen evolution reaction test or the electrocatalytic oxygen evolution reaction test. 2 This indicates that the electrocatalyst material in this comparative example exhibits very poor activity during the electrolysis reaction, and the electrocatalytic performance is much lower than that of the embodiments and comparative examples.

[0077] Comparative Example 2

[0078] A method for preparing a fully seawater electrocatalytic material comprises the following steps:

[0079] The nickel foam was cut into 2cm×3cm size, and the cut nickel foam was ultrasonically cleaned in 1mol / L HCl solution, deionized water and anhydrous ethanol for 30min respectively, pretreated to remove oxides and other impurities on the surface of the nickel foam, and vacuum dried at 60℃ for subsequent use; 1.0mmol Co(NO3)3·6H2O was dissolved in 40mL deionized water under stirring, and the obtained Co(NO3)3 solution was transferred to a 50mL polytetrafluoroethylene liner, and then the pretreated nickel foam was inserted into the Co(NO3)3 solution, and the liner was sealed and transferred to a stainless steel reactor and sealed; reacted at 160℃ in an electric constant temperature blast oven for 10h, and then naturally cooled to room temperature; the reactor was taken out, the obtained product was rinsed with deionized water 3 times, and dried at 60℃ for 8h to obtain a Co3O4 / NF precursor composite material, which is a complete seawater electrocatalytic material.

[0080] The electrocatalytic material obtained in this comparative example was applied to electrocatalytic cracking of seawater in a simulated seawater solution, and the hydrogen evolution performance and oxygen evolution performance were tested as described in Example 1.

[0081] The electrocatalytic material prepared in this comparative example reached 100 mA / cm 2 The current density required an overpotential of 415mV; when conducting the electrocatalytic oxygen evolution reaction test, it reached 100mA / cm 2 The current density requires an overpotential of 452 mV, and the overpotential values ​​are significantly higher than those in Example 1, indicating that the catalytic performance of this comparative example is significantly lower than that in Example 1.

[0082] Comparative Example 3

[0083] A method for preparing a fully seawater electrocatalytic material comprises the following steps:

[0084] (1) Cut the nickel foam into 2cm×3cm size, ultrasonically clean the cut nickel foam in 1mol / L HCl solution, deionized water and anhydrous ethanol for 30min respectively, pre-treat to remove oxides and other impurities on the surface of the nickel foam, and vacuum dry at 60℃ for subsequent use; 2.0mmol Co(NO3)3·6H2O and 2.0mmol Na2MoO4·2H2O are dissolved in 40mL deionized water under stirring conditions, and the obtained uniform mixed solution is transferred to a 50mL polytetrafluoroethylene liner, and the pre-treated nickel foam is inserted into the above mixed solution, and the liner is sealed and transferred to a stainless steel reactor, which is sealed. React in an electric constant temperature blast oven at 120℃ for 8h, then naturally cool to room temperature, and finally take out the reactor, rinse the obtained product with deionized water 3 times, and dry it at 60℃ for 8h to obtain a CoMoO4 / NF composite material, which is a complete seawater electrocatalytic material.

[0085] The electrocatalytic material obtained in this comparative example was applied to electrocatalytic cracking of seawater in a simulated seawater solution, and the hydrogen evolution performance and oxygen evolution performance were tested as described in Example 1.

[0086] The electrocatalytic material prepared in this comparative example reached 100 mA / cm 2 The current density required an overpotential of 442 mV; when conducting the electrocatalytic oxygen evolution reaction test, it reached 100 mA / cm 2 The current density requires an overpotential of 415 mV, and the overpotential values ​​are significantly higher than those in Example 1, indicating that the catalytic performance of this comparative example is lower than that in Example 1.

[0087] Comparative Example 4

[0088] A method for preparing a fully seawater electrocatalytic material comprises the following steps:

[0089] (1) The nickel foam was cut into 2 cm × 3 cm sizes, and the cut nickel foam was ultrasonically cleaned in 1 mol / L HCl solution, deionized water, and anhydrous ethanol for 30 min respectively to remove oxides and other impurities on the surface of the nickel foam, and then vacuum dried at 60 ° C for subsequent use; 1.0 mmol Co(NO3)3·6H2O was dissolved in 40 mL deionized water under stirring, and the obtained Co(NO3)3 solution was transferred to a 50 mL polytetrafluoroethylene liner, and then the pretreated nickel foam was inserted into the Co(NO3)3 solution. The liner was sealed and transferred to a stainless steel reactor and sealed; the reaction was carried out at 160 ° C in an electric constant temperature forced air oven for 10 h, and then naturally cooled to room temperature; the reactor was taken out, the obtained product was rinsed with deionized water 3 times, and dried at 60 ° C for 8 h to obtain a Co3O4 / NF precursor composite material.

[0090] (2) Dissolve 2.0mmol of Co(NO3)3·6H2O and 2.0mmol of Na2MoO4·2H2O in 40mL of deionized water under stirring, transfer the obtained uniform mixed solution to a 50mL polytetrafluoroethylene liner, insert the Co3O4 / NF precursor composite material obtained in step (1) into the above mixed solution, seal the liner and transfer it to a stainless steel reactor, seal it, react at 120°C in an electric constant temperature blast oven for 8h, cool naturally to room temperature, take out the reactor, rinse the obtained product with deionized water 3 times, and dry it at 60°C for 8h to obtain a CoMoO4 / Co3O4 / NF composite material, which is a seawater electrocatalytic material.

[0091] The electrocatalytic material obtained in this comparative example was applied to electrocatalytic cracking of seawater in a simulated seawater solution, and the hydrogen evolution performance and oxygen evolution performance were tested as described in Example 1.

[0092] The SEM image of the sample of this comparative example is as follows Fig.12 As shown, it can be seen that the morphology of the sample is a nanorod structure, the length of the rod is 8-10 μm, and the width is 300-400 nm, which can increase the exposure of the active area to a certain extent. The electrocatalytic material prepared in this comparative example reaches 100 mA / cm when conducting the electrocatalytic hydrogen evolution reaction test. 2 The current density required an overpotential of 354mV; when conducting the electrocatalytic oxygen evolution reaction test, it reached 100mA / cm 2 The current density requires an overpotential of 391 mV, and the overpotential values ​​are higher than those in Example 1, indicating that the catalytic performance of this comparative example is lower than that in Example 1.

[0093] Comparative Example 5

[0094] A method for preparing a carbonate-doped fully-dissolved seawater electrocatalytic material comprises the following steps:

[0095] (1) The nickel foam was cut into 2 cm × 3 cm sizes, and the cut nickel foam was ultrasonically cleaned in 1 mol / L HCl solution, deionized water, and anhydrous ethanol for 30 min respectively to remove oxides and other impurities on the surface of the nickel foam, and then vacuum dried at 60 ° C for subsequent use; 1.0 mmol Co(NO3)3·6H2O was dissolved in 40 mL deionized water under stirring, and the obtained Co(NO3)3 solution was transferred to a 50 mL polytetrafluoroethylene liner, and then the pretreated nickel foam was inserted into the Co(NO3)3 solution. The liner was sealed and transferred to a stainless steel reactor and sealed; the reaction was carried out at 160 ° C in an electric constant temperature forced air oven for 10 h, and then naturally cooled to room temperature; the reactor was taken out, the obtained product was rinsed with deionized water 3 times, and dried at 60 ° C for 8 h to obtain a Co3O4 / NF precursor composite material.

[0096] (2) Dissolve 2.0mmol of urea and 0.5mmol of sodium citrate in 40mL of deionized water under stirring, transfer the obtained uniform mixed solution to a 50mL polytetrafluoroethylene liner, insert the Co3O4 / NF precursor composite material obtained in step (1) into the above mixed solution, seal the liner and transfer it to a stainless steel reactor, seal it. React in an electric constant temperature blast oven at 120℃ for 8h, cool naturally to room temperature, take out the reactor, rinse the obtained product with deionized water 3 times, and dry it at 60℃ for 8h to obtain CO3 2- -Co3O4 / NF composite material, that is, carbonate-doped full seawater electrocatalytic material.

[0097] The electrocatalytic material obtained in this comparative example was applied to electrocatalytic cracking of seawater in a simulated seawater solution, and the hydrogen evolution performance and oxygen evolution performance were tested as described in Example 1.

[0098] The SEM image of the sample of this comparative example is as follows Fig.13 As shown, it can be seen that the morphology of the sample is a nanoparticle structure, and the size of the nanoparticles is 80-100nm. The generation of nanoparticles increases the roughness of the current collector surface, which improves its catalytic performance to a certain extent. The electrocatalytic material prepared in this comparative example reaches 100mA / cm when conducting the electrocatalytic hydrogen evolution reaction test. 2 The current density required an overpotential of 395mV; when conducting the electrocatalytic oxygen evolution reaction test, it reached 100mA / cm 2 The current density requires an overpotential of 465 mV, and the overpotential values ​​are significantly higher than those in Example 1, indicating that the catalytic performance of this comparative example is much lower than that in Example 1.

[0099] Comparative Example 6

[0100] A method for preparing a carbonate-doped fully-dissolved seawater electrocatalytic material comprises the following steps:

[0101] (1) Cut the nickel foam into 2cm×3cm size, ultrasonically clean the cut nickel foam in 1mol / L HCl solution, deionized water and anhydrous ethanol for 30min respectively, pre-treat to remove oxides and other impurities on the surface of the nickel foam, and vacuum dry at 60℃ for subsequent use; 2.0mmol Co(NO3)3·6H2O, 2.0mmol Na2MoO4·2H2O, 2.0mmol urea and 0.5mmol sodium citrate are dissolved in 40mL deionized water under stirring conditions, and the uniform mixed solution is transferred to a 50mL polytetrafluoroethylene liner, and then the pre-treated nickel foam is inserted into the above mixed solution, the liner is sealed and transferred to a stainless steel reactor, and sealed. React at 120℃ in an electric constant temperature blast oven for 8h, then naturally cool to room temperature, and finally take out the reactor, rinse the obtained product with deionized water 3 times, and dry it at 60℃ for 8h to obtain CO3 2- -CoMoO4 / NF composite material is a carbonate-doped full seawater electrocatalytic material.

[0102] The electrocatalytic material prepared in this comparative example was applied to the electrocatalytic cracking of seawater in a simulated seawater solution, and the hydrogen evolution performance and oxygen evolution performance were tested as described in Example 1.

[0103] The SEM image of the sample of this comparative example is as follows Fig.14 As shown, it can be seen that the morphology of the sample is a hydrangea-shaped nanoflower structure, which is similar to the morphology of Example 1, wherein the diameter of the hydrangea-shaped CoMoO4 nanoflower is 3±1 μm. The electrocatalytic material prepared in this comparative example reaches 100 mA / cm 2 The current density required an overpotential of 404mV; when conducting the electrocatalytic oxygen evolution reaction test, it reached 100mA / cm 2 The current density requires an overpotential of 418 mV, and the overpotential values ​​are higher than those in Example 1, indicating that the catalytic performance of this example is lower than that in Example 1.

Claims

1. A method for preparing a carbonate-doped high-activity seawater electrocatalytic material, comprising the following steps: (1) placing the pretreated nickel foam (NF) current collector in a cobalt source aqueous solution for hydrothermal reaction; after the reaction is completed, cooling, washing, and drying to obtain a Co3O4 / NF precursor composite material; (2) placing the Co3O4 / NF precursor composite material obtained in step (1) in a mixed solution containing a cobalt source, a molybdenum source, urea and sodium citrate to carry out a hydrothermal reaction; after the reaction is completed, cooling, washing and drying are performed to obtain CO3 2- -CoMoO4 / Co3O4 / NF heterogeneous composite material, that is, a carbonate-doped high-activity electrocatalytic material for the complete decomposition of seawater.

2. The method for preparing the carbonate-doped high-activity seawater electrocatalytic material according to claim 1, characterized in that: The pretreatment step in step (1) is: ultrasonically treating the nickel foam current collector in 1 mol / L HCl solution, deionized water, and anhydrous ethanol for 30 min respectively, and then vacuum drying at 60° C. for later use; The thickness of the nickel foam is 1.5-2.0 mm.

3. The method for preparing the carbonate-doped high-activity seawater electrocatalytic material according to claim 1, characterized in that: The cobalt source in step (1) is Co(NO3)3·6H2O, and the concentration of the cobalt source aqueous solution is 0.02-0.03 mol / L.

4. The method for preparing the carbonate-doped high-activity seawater electrocatalytic material according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (1) is 150-180° C., and the hydrothermal reaction time is 10-12 hours; the washing is performed by rinsing with deionized water for 3-5 times, and the drying is performed at 60-70° C. for 6-8 hours.

5. The method for preparing the carbonate-doped high-activity seawater electrocatalytic material according to claim 1, characterized in that: In step (2), the cobalt source is Co(NO3)3·6H2O, and the molybdenum source is Na2MoO4·2H2O.

6. The method for preparing the carbonate-doped high-activity seawater electrocatalytic material according to claim 1, characterized in that: The concentration of the cobalt source in the mixed solution in step (2) is 0.04-0.06 mol / L.

7. The method for preparing the carbonate-doped high-activity seawater electrocatalytic material according to claim 1, characterized in that: In the mixed solution of step (2), the molar ratio of the molybdenum source to the cobalt source is 1:1, the molar ratio of urea to the cobalt source is 0.75-1.25:1, and the molar ratio of sodium citrate to the cobalt source is 0.2-0.3:

1.

8. The method for preparing the carbonate-doped high-activity seawater electrocatalytic material according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (2) is 120-140° C., and the time of the hydrothermal reaction is 8-10 hours; the washing is performed by rinsing with deionized water for 3-5 times, and the drying is performed at 60-70° C. for 6-8 hours.

9. A carbonate-doped high-activity seawater electrocatalytic material prepared by the preparation method of claim 1, characterized in that: The electrocatalytic material comprises a nickel foam current collector and a heterogeneous composite material CO3 in situ grown on the nickel foam current collector. 2- -CoMoO4 / Co3O4; the heterogeneous composite material CO3 2- -The microstructure of CoMoO4 / Co3O4 is a combination of carbonate-doped hydrangea-shaped CoMoO4 nanoflowers and Co3O4 nanoparticles.

10. The use of the carbonate-doped high-activity seawater electrocatalytic material according to claim 9, characterized in that: As a seawater electrocatalyst, it is used for electrocatalytic decomposition of seawater.

Citation Information

Patent Citations

  • NiMoO4@Co3O4 core-shell nano composite material, and preparation method and application thereof

    CN111268745A

  • Bifunctional heterostructure catalyst, preparation method and application of bifunctional heterostructure catalyst in electrolyzed water

    CN119186650A

Cited By

  • Preparation method and application of ferronickel phosphide coated nickel telluride nanorod material

    CN120844121A

  • Preparation of phosphate-modified carbon quantum dot nickel-based catalyst and use thereof in alkaline seawater electrolysis

    WO2026166566A1